2022
DOI: 10.1177/03635465221107085
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel Multimodal Imaging Technique to Model In Vivo Quadriceps Force and ACL Strain During Dynamic Activity

Abstract: Background: Quadriceps loading of the anterior cruciate ligament (ACL) may play a role in the noncontact mechanism of ACL injury. Musculoskeletal modeling techniques are used to estimate the intrinsic force of the quadriceps acting at the knee joint. Purpose/Hypothesis: The purpose of this paper was to develop a novel musculoskeletal model of in vivo quadriceps force during dynamic activity. We used the model to estimate quadriceps force in relation to ACL strain during a single-leg jump. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain 2-6,8,9,22-24 and puts the ligament at increased risk for injury. As noted previously, these techniques have advantages over cadaveric studies, which may not accurately reproduce in vivo loading conditions, 7 and videographic techniques, which may be susceptible to errors due to the viewpoint of the camera 3 and skin motion artifact.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain 2-6,8,9,22-24 and puts the ligament at increased risk for injury. As noted previously, these techniques have advantages over cadaveric studies, which may not accurately reproduce in vivo loading conditions, 7 and videographic techniques, which may be susceptible to errors due to the viewpoint of the camera 3 and skin motion artifact.…”
Section: Discussionsupporting
confidence: 90%
“…15 Specifically, this study suggested that the knee was in a straight position in both the sagittal (\20°of flexion) and coronal (\10°of valgus) planes and underwent large anterior tibial translation (.20 mm) near the time of ACL rupture for both bone bruise patterns. 15 We believe that our previous work using imaging techniques to quantify in vivo ACL elongation and joint motion supports the findings of the present study, in that the previous studies suggested that knee extension elevates ACL strain [2][3][4][5][6]8,9,[22][23][24] and puts the ligament at increased risk…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that quadriceps activity increases prior to landing from a jump. 16,30,50,78 This portion of the jump is when we observed elevated ACL strain, suggesting that quadriceps forces may load the ACL prior to landing. Thus, in the event of landing on an extended knee with unanticipated timing, the ACL is primed with increased tension and therefore more susceptible to rupture.…”
Section: Discussionmentioning
confidence: 79%
“…1,69 After the MRI, participants were imaged using highspeed biplanar radiography (matrix size, 1152 3 1152 pixels 2 ; frame rate, 120 Hz; pulse width, 1.0-1.5 ms), as previously described. 27,[30][31][32][33] Briefly, the participant was positioned within the field of view of the sources and intensifiers, which were adjusted to minimize obstruction from the contralateral limb. Next, calibration images were collected to correct for image distortion and to define the (C) The wireframe models were used to generate 3D models of the bones, including the femoral and tibial attachment sites of the anterior cruciate ligament.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, when the knee is extended, the patellar tendon is oriented to apply an anteriorly directed shear force to the proximal tibia. 13,17,18,20 As the flexion angle increases, the patellar tendon applies a posteriorly directed shear force on the tibia. Together with these investigations of in vivo ACL strain as a function of knee flexion angle, 15,[17][18][19] the findings of the present study suggest that landing on an extended knee is a high-risk position for ACL rupture for both those with 3 and 4 bone bruises.…”
Section: Discussionmentioning
confidence: 99%